15th Annual Conference of Applied Mathematics, Univ. of Central Oklahoma, Electronic Journal of Differential Equations, Conference 02, 1999, pp. 61–74. ISSN: 1072-6691. URL: http://ejde.math.swt.edu or http://ejde.math.unt.edu ftp ejde.math.swt.edu or ejde.math.unt.edu (login: ftp) THEOREMS ON n-DIMENSIONAL LAPLACE TRANSFORMS AND THEIR APPLICATIONS R. S. Dahiya & Jafar Saberi-Nadjafi Abstract. In the present paper we prove certain theorems involving the classical Laplace transform of n-variables. The theorems are then shown to yield a nice algorithm for evaluating n-dimensional Laplace transform pairs. In the second part, boundary value problems are solved by using the double Laplace transformation. 1. Introduction and Notation The generalization of the well-known Laplace transform R∞ L[f (t); s] = 0 e−st f (t)dt to n-dimensional is given by Z Ln [f (t̄); s̄] = ∞ 0 Z ∞ 0 Z ··· 0 ∞ exp(−s̄ · t̄)f (t̄)Pn (dt̄) where t̄ = (t1 , t2 , . . . , tn ), s̄ = (s1 , s2 , . . . , sn ), s̄ · t̄ = n P i=1 n Q si ti and Pn (dt̄) = dtk . k=1 In addition to the notations introduced above, we will use the following throughout this article. Let tv = (tv1 , tv2 , . . . , tvn ) for any real exponent v and let pk (t) be the k-th symmetric polynomial in the components tk of t. Then (i) p1 (tv ) = tv1 + tv2 + · · · + tvn (ii) pn (tv ) = tv1 · tv2 . . . tvn . 2. Main Results Theorem 2.1. Suppose that f (x) and f (x2 ) are functions of class Ω. Let L{f (x); s} = φ(s), 1 − 32 L{x φ x ; s} = ξ(s), 1 L{x− 2 ξ x12 ; s} = ζ(s), and L{f (x2 ); s} = G(s), 3 1 u − 12 − 32 where x− 2 φ x1 and x are also functions of class Ω, x f (u) ξ exp −sx − 2 x x 1 1 3 2 and u− 2 x− 2 exp −sx − 2ux f (u) belong to L1 [(0, ∞) × (0, ∞)]. (i) (ii) (iii) (iv) 1991 Mathematics Subject Classifications: 44A30. Key words and phrases: multi-dimensional Laplace transforms. c 1999 Southwest Texas State University and University of North Texas. Published November 24, 1999. 61 R. S. Dahiya & Jafar Saberi-Nadjafi 62 Then n−2 2 1 π 1 G[2p1 (x−1 )]; s = p x2 2 n Ln 1 p1 s 2 2 1 1 ζ P1 s 2 , · pn s 2 (2.1) h 1 i where Re p1 s 2 > d, a constant, provided the integrals involved exist for n = 2, 3, . . . , N . The existence conditions for two-dimensions are given in Ditkin and Prudnikov [11; p.4] and similar conditions hold for N -dimensions, we refer to Brychkov et al. [2; Ch.2]. Proof. Using (i) and (ii), we obtain Z ∞ Z ∞ ξ(s) = x 0 − 32 0 u exp −sx − f (u)du dx. x (2.2) Next we wish to interchange the order of the integral on the right side of (2.2). The 3 integrand x− 2 exp −sx − ux f (u) belongs to L1 [(0, ∞) × (0, ∞)], that, by Fubini’s Theorem, interchanging the order of the integral on the right of (2.2) is permissible. Therefore, Z ∞ Z ∞ h 3 ui ξ(s) = f (u) x− 2 exp −sx − dx du (2.3) x 0 0 We then use a well-known result in Robert and Kaufman [15] on the right side of (2.3) to obtain Z ∞ 1 1 1 1 ξ(s) = π 2 (2.4) u− 2 exp −2u 2 s 2 f (u)du. 0 Using (2.4) and (iii), it follows that ζ(s) = π 1 2 Z ∞ Since x ∞ x 0 − 12 Z u − 12 − 12 u − 12 0 exp −sx − 2u 12 exp −sx − x 1 2u 2 f (u)du dx., where Re s > λ1 . (2.5) belongs to L1 [(0, ∞) × (0, ∞)]; therefore, accord- x ing to Fubini’s Theorem, (2.5) can be rewritten as 1 Z ∞ ζ(s) = π 2 0 1 u− 2 f (u) Z ∞ 0 3 2 1 4 2 u 1 x− 2 exp −sx − 4x 2 dx du, where Re s > λ1 . From the tables of Roberts and Kaufman [15], we obtain Z 1 2 ∞ s ζ(s) = π 0 3 1 1 1 u− 2 f (u) exp −2 2 u 4 s 2 du. (2.6) Next, we substitute u = v 2 in (2.6) to obtain 1 2 Z ∞ s ζ(s) = 2π 0 3 1 1 exp −2 2 s 2 v 2 f (v 2 )dv. (2.7) n-dimensional Laplace transforms 63 1 h 1 i2 Replacing s by p1 s 2 , multiplying both sides of (2.7) by pn s 2 , we obtain Z 1 1 h 1 i 2 2 2 p1 s pn s ζ p1 s = 2π ∞ 0 1 h 3 1 1i pn s 2 exp −2 2 p1 s 2 v 2 f (v 2 )dv (2.8) Now we use the operational relation given in Ditkin and Prudnikov [11] 1 1 a2 − 12 2 2 si exp −asi + (πxi ) exp − for i = 1, 2, . . . , n 4xi Equation (2.8) reads as follows 1 1 1 2 n pn s 2 p1 s 2 ζ p1 s 2 = n 2 π n−2 2 1 pn x 2 Z ∞ 0 (2.9) exp −2vp1 x−1 f (v 2 )dv (2.10) Applying (iv) in (2.10), we arrive at 1 1 1 2 n pn s 2 p1 s 2 ζ p1 s 2 = n i h −1 . G 2p x 1 n−2 1 π 2 pn x 2 2 Therefore, 1 n−2 i h s2 p 2 1 1 π 2 1 1 1 G 2p1 x 2 ; s = 1 ζ p1 s 2 Ln , · p x2 2 pn s 2 n where n = 2, 3, . . . , N . To show the applicability of Theorem 2.1, we will construct certain functions with n variables and calculate their Laplace transformation. τ −1 Example 2.1. Assume that f (x) = x 4 . Then Γ τ +3 4 φ(s) = , Re s > 0, Re v > −3; τ +3 s 4 τ +1 Γ τ +3 Γ 4 4 ξ(s) = , Re τ > −1, Re s > 0, and τ +1 s 4 Γ τ +3 Γ τ +1 Γ τ2 + 1 4 4 ζ(s) = , Re s > 0, Re τ > −1. τ s 2 +1 Γ τ +1 2 G(s) = , Re τ > −1. τ +1 s 2 Therefore, 1 Ln ; 1h i τ +2 2 pn x 2 p1 x−1 h where Re τ > −1, Re p1 s 1 2 s =π n−1 2 Γ τ 3 + 2 2 · 1 1 h 1 iτ +2 pn s 2 p1 s 2 (2.11) i > 0, and n = 2, 3, . . . , N . R. S. Dahiya & Jafar Saberi-Nadjafi 64 1 Example 2.2. Suppose that f (x) = I0 (ax 2 ). Then 2 1 a φ(s) = exp , Re s > 0, s 4s 1 ξ(s) = π2 2 1 , Re s > Re a2 , 4 s − a4 2 ( "3 # "3 #) 2 ; s2 ; s2 Γ 14 s 4π 4π 4 4 ζ(s) = 5 . 2 1 F2 1 5 2 − 1 F2 3 7 a2 a 6π a2 Γ 14 , ; , ; 2 4 2 4 1 G(s) = 1 , Re s > |Re a|. (s2 − a2 ) 2 So that 1 1 i1 ; s pn (x ) 4p2 x−1 − a2 2 1 1 1 n 2 3 2 2π 2 p1 s 2 4π Γ p ; 1 s 4 − = 5 1 F 2 1 2 1 5 a2 a 2 pn s 2 Γ 14 2, 4; 1 2 5 s2 p ; 1 4 ;s , 1 F2 3 7 a2 2, 4; h 1 i where Re p1 s 2 > |Re a|. " # (a)p ; Example 2.3. Consider f (x) = p Fq cx . Then (b) ; q " # (a)p ; φ(s) = 1s p+1 Fq cx , (b)q ; where p ≤ q, Re s > |Re c|. " # 1 (a)p , 1, 12 ; c π2 ξ(s) = 1 p+2 Fq , s2 (b)q ;s Ln 1 2 ·h 1 4 2 1 p21 s 2 (2.12) 6π where p ≤ q − 1, Re τ > 0 if p + 1 < q, Re s > Re c if p + 1 = q, " # (a)p , 1, 12 , 34 , 54 ; 4c π ζ(s) = 3 p+4 Fq , 2s 2 (b)q ; s2 1 where p ≤ q − 3; Re s > 0 if p ≤ q − 4; and Re(s + 2c 2 cos πr) > 0 (r = 0, 1) if p = q − 3. Hence (a)p , 1, 12 ; 1 c 1h i p+2 Fq ;s Ln p x 2 p x−1 (b)q ; p21 x−1 n 1 n 1 3 5 (a) , 1, , , ; 2 p π 4c 2 4 4 1 1 p+4 Fq 1, = (b)q ; p41 s 2 2pn s 2 p21 s 2 (2.13) n-dimensional Laplace transforms h 1 h 1 i i 1 > 0 if p ≤ q − 4; and Re p1 s 2 + 2c 2 cos πr where p ≤ q − 3, Re p1 s 2 > 0(r = 0, 1) if p = q − 3. 1 65 1 Example 2.4. Assume that f (x) = x 2 J0 (ax 2 ). Then "3 # 1 π2 a2 2; φ(s) = 3 1 F1 − , Re s > 0, 4s 2s 2 1; "3 # 1 π2 a2 a2 2 , 1; ξ(s) = − F , Re s > −Re − , 2 1 2 4s 4 1 ; ! 1 3 1 1 a2 4 , 4 , 0, − 2 1,4 ζ(s) = 1 1 G4,2 , s2 π 2 s2 0, 0 where Re s > 0, | arg a| < 2π. "3 # 1 2 , 1; π2 a a2 2 G(s) = − , Re s > Re − . 2 F1 2 4s 4 1 ; Hence x−1 p1 h i3 , s p x 12 4p2 x−1 + a2 2 n 1 1 n−3 1 3 1 π 2 p1 s 2 2 , , 0, − a 2 2 4 1 G1,4 = , 4,2 1 4 0, 0 pn s 2 p1 s 2 Ln (2.14) h 1 i where Re p1 s 2 > 0, | arg a| < 2π and G1,4 4,2 is a Meijer’s G-function. Example 2.5 (Two-Dimensions). Upon substituting n = 2 in Examples 2.1, 2.2, 2.3, and 2.5 we arrive at the following results, respectively ( ) τ τ (xy) 2 1 1 L2 = π2Γ (2.15) +1 · 1 τ +1 τ +1 ; s1 , s2 1 1 2 (x + y) 2 (s1 s2 ) 2 s12 + s22 h 1 i 1 where Re τ > −1, Re s12 + s22 > 0. ( L2 1 (xy) 2 ) 1 ; s1 , s2 [4(x + y)2 − (axy)2 ] 2 1 2 1 1 1 2 2 2 2 3 2π s1 + s2 4π 4 ; s1 + s2 = 1 2 1 F2 1 5 5 1 a2 a 2 (s1 s2 ) 2 , ; Γ 4 2 4 2 2 1 1 1 1 2 12 2 2 5 Γ 4 s1 + s22 + s s 1 2 4 ; − F 1 2 3 7 6π a2 2, 4; (2.16) R. S. Dahiya & Jafar Saberi-Nadjafi 66 h 1 i 1 where Re s12 + s22 > 0, | arg a| < 2π. ( " # ) 1 (a)p , 1, 12 ; c(xy)2 (xy) 2 L2 ; s1 , s2 p+2 Fq 2 x+y (b)q ; (x + y) 1 3 5 π 4c (a)p , 2 , 4 , 4 ; = F q 1 4 , p+4 2 1 1 1 1 (b)q ; s12 + s22 2(s1 s2 ) 2 s12 + s22 (2.17) h 1 i h 1 i 1 1 1 where p ≤ q − 3, Re s12 + s22 > 0 if p ≤ q − 4; and Re s12 + s22 + 2c 2 cos πr > 0(r = 0, 1) if p = q − 3. ( L2 ) 3 2 (xy) (x + y) 3 [4(x + y)2 + (axy)2 ] 2 h 1 2 1 2 i ; s1 , s2 where R s1 + s2 > |Re a| and 1 3 1 2 , 2 , 0, − 2 a2 s + s2 1,4 = 1 , 1 G4,2 1 4 1 (πs1 s2 ) 2 0, 0 2 2 s1 + s2 1 2 1 2 (2.18) G1,4 4,2 is a Meijer’s G-function. Remark 2.1. If we let τ = 0 in Relation (2.15), and then using Relation (1) in [24]. We deduced that 1 1 1 2 2 2 n o s π + s + s s 1 2 1 2 1 1 L2 (x + y) 2 ; s1 , s2 = (2.19) 1 3 2(s1 s2 ) 2 s12 + s22 Theorem 2.2. Assume that f belongs to class Ω and φ be the one-dimensional Laplace transformation of f . Let n 1 o (i) L x− 2 φ x1 ; s = γ(s), −v d (ii) − ds s γ s12 = ζ(s), (iii) L {xf (x); s} = H(s), −v 1 d and suppose that x− 2 φ x1 belongs to Ω and ds s γ s12 exists for Re s > c1 where c1 is a constant. Then i h i h (v − 1)φ p1 x−1 − 2p1 x−1 H p1 x−1 1 Ln ;s = pn x 2 n−1 −1 π 2 1 1 h 1 iv ζ p1 s 2 , pn s 2 p1 s 2 (2.20) h 1 i where Re p1 s 2 > d, a constant n = 2, 3, . . . , N . It is asssumed that the integral on the left exists. Proof. A similar method to Theorem 2.2 can be used to prove this theorem. The outline of the proof is as follows. n-dimensional Laplace transforms 67 Making use of our hpothesis and (i) yields Z ∞ Z ∞ 1 1 u γ(s) = π 2 x− 2 exp −sx − f (u)du dx, where Re s > c1 . x 0 0 (2.21) Using Fubini’s Theorem to interchange the order of the integral on the right side of (2.21) and applying a result in Roberts and Kaufman [15] we obtain Z ∞ 1 1 1 1 2 γ(s) = π (2.22) f (u)s− 2 exp −2u 2 s 2 du. 0 Taking into account the condition (ii) we see that the equation (2.22) implies that ! Z ∞ Z ∞ 1 2 1 1 1 2u v −1 2 2 s ζ(s) = π (v − 1) f (u) exp − u 2 f (u) du − 2π s s 0 0 ! 1 −2u 2 exp (2.23) du, where Re s > c1 . s h 1 i−1 Now. replacing s by p1 s 2 and then multiplying each side of (2.23) by 1 pn s 2 and then making use of operational relations (2.9) and (2.24) a 1 3 1 a2 −2 −2 2 si exp −asi + π xi exp − for i = 1, 2, . . . , n, (2.24) 2 4xi equation (2.23) reads 1 h 1 i−v 1 −1 n pn s 2 p1 s 2 ζ p1 s 2 = n 1 n−1 2 Z (v − 1) 1 ∞ f (u) 0 pn x 2 h i Z ∞ i h exp −up1 x−1 dx − 2p1 x−1 uf (u) exp −up1 x−1 du. π 0 (2.25) Equation (2.25) with (iii) and the definition of the one-dimensional Laplace transform, leads to 1 h 1 i−v 1 −1 pn s 2 p1 s 2 ζ p1 s 2 n = n Therefore, i h io n h −1 −1 H p −1 − 2p . (v − 1)φ p x x x 1 1 1 n−1 1 π 2 pn x 2 1 i h i h (v − 1)φ p1 x−1 − 2p1 x−1 H p1 x−1 1 Ln ;s pn x 2 n−1 −1 π 2 1 1 h 1 iv ζ p1 s 2 = , pn s 2 pn s 2 h 1 i where Re p1 s 2 > d for some constant d, n = 2, 3, . . . , N . R. S. Dahiya & Jafar Saberi-Nadjafi 1 Example 2.6. Let f (x) = J0 2x 2 . Then 68 1 1 φ(s) = exp − , Re s > 0, s s 1 π2 γ(s) = Thus 3 2(s + 1) 2 , Re s > −1. 1 ζ(s) = π 2 (vs2 + v − 3) 5 2sv−2 (1 + s2 ) 2 , Re s > −1. Therefore 1 1 1 −1; Ln exp − (v − 1) − 21 F1 ;s 1; p x−1 p x−1 p x 12 p1 x−1 1 n 1 1h 1 i n h 1 i π 2 p1 s 2 v + (v − 3)p21 s 2 = > −1. , where Re p1 s 2 1h 1 i 52 2 2 2 1 + p1 s 2pn s (2.26) Remark 2.2. If we let n = 2 and v = 1 or v = 3, from the equation (2.26) we deduce the following results, respectively ( ) 1 (xy) 2 xy −1; xy (i) L2 exp − ; s1 , s2 = 1 F1 1; x + y (x + y) x+y 1 1 2 1 1 2 2 2 2 π s1 + s2 2 s1 + s2 −1 (2.260 ) 52 , 2 1 1 1 4(s1 s2 ) 2 1 + s12 + s22 h 1 i 1 where Re s12 + s22 > −1. ( (ii) ) 1 (xy) 2 xy −1; xy L2 exp − 1 − 1 F1 ; s1 , s2 = 1; x + y (x + y) x+y 1 1 3π s12 + s22 , 1 2 52 1 1 2 2 2(s1 s2 ) 2 1 + s1 + s2 (2.2600 ) h 1 i 1 where Re s12 + s22 > 1. Notice, with the help of (2.260 ) from (2.2600 ) we arrive at the following result 1 1 ( ) 2 2 1 + s s 1 2 (xy) 2 π xy 000 L2 exp − ; s1 , s2 = 23 . (2.26 ) (x + y) x+y 2 2 1 1 1 (s1 s2 ) 2 1 + s12 + s22 n-dimensional Laplace transforms 69 This is the same as the result (2.109) in Ditkin and Prudnokov [11; p. 140]. Furthermore, with the help of (2.26000 ) and the operational relation (47) in Voelker and Doetsch [24; p. 159], we derive the following new results. L2 1 y 2 x h 1 xy · exp − ; s1 , s2 = x+y x+y 1 2 Re s12 + s22 > 1. ( 1 ) x 2 1 xy L2 · exp − ; s1 , s2 = y x+y x+y 1 2 1 2 1 2 1 2 2 12 , (2.26iv ) 1 2 s1 h s2 1 + s1 + s2 i 1 1 π π 1 2 12 1 2 2 1 + s1 + s2 , (2.26v ) i where Re s1 + s2 > 1. 1 1 Example 2.7. Assuming x− 2 cos 2x 2 , we obtain π 12 1 exp − x , Re s > 0. s π γ(s) = , Re s > −1. s+1 π 12 s−v+1 2 ζ(s) = vs + v − 2 , Re s > −1. (s2 + 1)2 1 π2 s 1 H(s) = 5 − 1 exp − , Re(s) > 0. s s2 2 φ(x) = Therefore, Ln −1 −1 − p1 x − 2 exp − (v − 1)p1 x h i 32 pn x−1 1 p1 ((x−1 ) ;s p1 n−1 1 n 1 o h 1 i π 2 p1 s 2 2 2 = (v − 2)p + v , Re p1 s 2 > 0. s 1h 1 i2 1 2 2 2 (2.27) 1 + p1 s pn s x−1 Remark 2.3. If we let n = 2 and v = 1 in (2.27) by using the following well-known formula 1 1 1 2 2 2 π s1 + s2 xy xy L2 − ; s1 , s2 = 3 exp 1 2 2 , x+y 1 (x + y) 2 1 (s1 s2 ) 2 1 + s12 + s22 h 1 i 1 Re s12 + s22 > 0. R. S. Dahiya & Jafar Saberi-Nadjafi 70 we derive that L2 1 (x + y) 1 2 exp − xy x+y ; s1 , s2 h 1 i 1 Re s12 + s22 > 0. 1 1 1 π 2 s12 + s22 = 1 2 , 1 1 2 2 (s1 s2 ) 2 1 + s1 + s2 (2.270 ) 3. Non-Homogeneous Second Order Partial Differential Equations of Parabolic type In this section we solved a few partial differential equations of the type uxx + 2uxy + uyy + u = f (x, y), 0 < x < ∞, 0 < y < ∞, (3.1) under the following initial and boundary conditions u(x, 0) = u(0, y) = uy (x, 0) = ux (0, y) = u(0, 0) = 0 (3.2) by means of some of our results established in Section 2 using the double Laplace transformation. Example 3.1. Determination of a solution u = u(x, y) of (3.1) and (3.2) for 1 (a) f (x, y) = (x + y) 2 τ (b) f (x, y) = (xy) 2 τ +1 (x+y) 2 τ (c) f (x, y) = (xy) 2 τ +2 (x+y) 2 We will use the following for the rest of this section. If u(x, 0) = f (x), u(0, y) = g(y), uy (x, y)|y=0 = uy (x, 0) = f1 (x), ux (x, y)|x=0 = ux (0, y) = g1 (y) and if their one-dimensional Laplace transformations are F (s1 ), G(s2 ), F1 (s1 ) and G1 (s2 ), respectively, then Z L2 {u(x, y); s1 , s2 } = L2 {uxx ; s1 , s2 } = L2 {uyy ; s1 , s2 } = ∞ 0 Z 0 ∞ exp(−s1 x − s2 y)u(x, y)dxdy = U (s1 , s2 ) s21 U (s1 , s2 ) − s1 G(s2 ) − G1 (s2 ) s22 U (s1 , s2 ) − s2 F (s1 ) − F1 (s1 ) L2 {uxy ; s1 , s2 } = s1 s2 U (s1 , s2 ) − s1 F (s1 ) − s2 G(s2 ) + u(0, 0) (3.3) (3.4) (3.5) (3.6) (a) By applying the double Laplace transformation termwise to partial differential equation and the initial-boundary condition in (3.1) and (3.2), using (3.3)–(3.6), n-dimensional Laplace transforms 71 and with the aid of Relation (2.19) in Remark 2.1, we obtain the transformed problem h i 1 1 2 2 i h 1 s + s + (s s ) π 1 2 1 2 1 1 2 2 U (s1 , s2 ) = , Re s + s · 1 1 1 2 > 0. 3 (s1 + s2 )2 + 1 2(s1 s2 ) 2 s12 + s22 (3.7) The inversion of (3.7) will provide us with the solution of (3.1) and (3.2). So that, the inverse transform of (3.7) can be obtained using formula (133) in [24] Z x u(x, y) = 0 1 (x + y − 2ξ) 2 sin ξdξ (3.8) By a simple change of variable x + y − 2ξ = 2t2 in (3.8), we obtain + 32 u(x, y) = 2 1 Z ( y−x 2 2 ) 1 2 ( x+y 2 ) x+y t sin t − 2 2 2 dt if y > x. Expanding the sine and making some simplification, we deduce that + 32 u(x, y) = 2 1 Z ( x−y 2 2 ) ( x+y 2 ) 1 2 cos x + y 2 Z ( y−x ) 12 2 1 2 ( x+y 2 ) 2 2 t sin t dt − sin x+y 2 (3.9) t2 cos t2 dt Calculating the integrals involved in (3.9), we arrive at u(x, y) = 1 4 x+y 2 12 − y−x 2 12 1 x+y 2 1 x+y 2 cos x + π 2 cos + π 2 sin C y−x 2 S y−x 2 −D −S x+y 2 x+y 2 if y > x, where C(·) and S(·) are Fresnel integrals. Similarly, to obtain the transform equations for parts (b) and (c). We replace Relation (2.19) in Example (2.5) for part (b) and (2.15) in the same example with Formula 181 in Brychkov et al. [2; p.300] for part (c) to arrive at +1 U (s1 , s2 ) = 1 τ +1 1 τ [(s1 + s2 )2 + 1] (s1 s2 ) 2 s12 + s22 1 π2Γ U (s1 , s2 ) = 2τ Γ τ +3 2 τ 2 πΓ(τ + 1) τ +1 , 1 1 [(s1 + s2 )2 + 1] s12 + s22 (3.10) (3.11) R. S. Dahiya & Jafar Saberi-Nadjafi 72 h 1 i 1 where Re s12 + s22 > 0. Thus, we obtain the following solutions, respectively u(x, y) = 1 2τ +1 Z y−x t − τ +1 2 2 τ t − (x − y)2 2 sin x+y t − (x + y) 2 dt if y > xRe v > −1. Z y−x 2 τ 1 t − (x + y) − τ +3 2 2 2 u(x, y) = τ +1 t − (x − y) t sin dt 2 2 x+y if y > x, Re v > −1. (3.12) (3.13) Remark 2.4. Substituting τ = 0 in parts (b) and (c), lead to uxx + 2uxy + uyy + u = uxx + 2uxy + uyy + u = 1 1 (3.14) 3 (3.15) (x + y) 2 1 (x + y) 2 Next, using (3.14) and (3.15), we arrive at the following explicit solutions for the equations (3.14) and (3.15) respectively π 12 x+y y−x x+y u(x, y) = cos S −S − 2 2 2 2 x+y y−x x+y sin C −C if y > x. 2 2 2 x+y y−x u(x, y) = cos S 1 cos(x + y) − 1 cos y − π 2 2 (x + y) 2 (y − x) 2 x+y x+y y−x x+y −S − sin C −C if y > x. 2 2 2 2 1 1 1 2 Example 3.2. Solve the following Parabolic differential equation described by 1 xy uxx + 2uxy + uyy + u = − , 0 < x < ∞, 0 < y < ∞, (3.16) 1 exp x+y (x + y) 2 under the initial and boundary conditions u(x, 0) = u(0, y) = uy (x, 0) = ux (0, y) = u(0, 0) = 0. (3.17) With the aid of (2.27’) in Remark 2.3 and the similar procedure we have followed for Example 3.1, the transformed problems reads 1 1 π s12 + s22 U (s1 , s2 ) = (3.18) i 12 , h 1 1 2 2 2 [(s1 + s2 ) + 1] 1 + s1 + s2 h 1 i 1 where Re s12 + s22 > 0. Using formula (133) in [24] the inverse transform of (3.18) leads to the following integral representation. 2 Z y−x t − (x + y)2 t − (x + y) − 12 u(x, y) = t exp sin dt if y > x. 4t 2 x+y n-dimensional Laplace transforms 73 References 1. Buschman, R.G., Heat transfer between a fluid and a plate: Multidimensional Laplace transformation methods, Internat. J. Math. & Math. Sci. 6 (1983), no. 3, 589–596. 2. Brychkov, Y.A., Glaeske, H.J., Prudnikov, A.P. and Tuan, V.K., Multidimensional Integral Transformations, Goddon and Breach, Philadelphia, 1992. 3. Churchill, R.V., Operational Mathematics, 3rd ed., McGraw-Hill Book Company, New York, 1972. 4. Dahiya, R.S., Certain Theorems on n-dimensional Operational Calculus, Compositio Mathematica, Amsterdam (Holland) 18 Fasc, 1,2, (1967), 17–24. 5. Dahiya, R.S., Computation of n-dimensional Laplace Transforms, Journal of Computational and Applied Mathematics 3 (1977), no. 3, 185–188. 6. Dahiya, R.S., Calculation of Two-dimensional Laplace Transforms pairs-I, Simon Stevin, A Quarterly Journal of Pure and Applied Mathematics 56 (1981), 97–108. 7. Dahiya, R.S., Calculation of Two-dimensional Laplace Transforms pairs-II, Simon Stevin, A Quarterly Journal of Pure and Applied Mathematics (Belgium) 57 (1983), 163–172. 8. Dahiya, R.S., Laplace Transform pairs of n-dimensions, Internat. J. Math. and Math. SCI 8 (1985), 449–454. 9. Dahiya, R.S. and Debnath, J.C., Theorems on Multidimensional Laplace Transform for Solution of Boundary Value Problems, Computers Math. Applications 18 (1989), no. 12, 1033–1056. 10. Dahiya, R.S. and Vinayagamoorthy, M., Laplace Transform pairs of n-Dimensions and Heat Conduction Problem, Math. Computer Modeling 13 (1990), no. 10, 35–50. 11. Ditkin, V.A. and Prudnikov, A.P., Operational Calculus In Two Variables and Its Applications, Pergamon Press, New York, 1962. 12. Estrin, T.A. and Higgins, T.J., The Solution of Boundary Value Problems by Multiple Laplace Transformations, Journal of the Franklin Institute 252 (1951), no. 2, 153–167. 13. Jaeger, J.C., The Solution of Boundary Value Problems by a Double Laplace Transforms, Bull. Amer. Math. Soc. 46 (1940), 687–693. 14. Magnus, W. and Oberhettinger, Formulas and Theorems for Special Functions of Mathematical Physics, Springer-Verlag, New York, Inc, 1966. 15. Roberts, G.E. and Kaufman, Tables of Laplace Transforms, W.B. Saunders Company, Philadelphia and London, 1966. 16. Pipes, L.S., The Operational Calculus, (I), (II), (III), Journal of Applied Physics 10 (1939), 172–180, 258–264 and 301–311. 17. Royden, H.L., Real Analysis, 3rd Ed., Macmillan Publishing Company, New York, 1988. 18. Saberi-Nadjafi, J., Theorems On N -dimensional Inverse Laplace Transformations, Proc. of the Eighth Annual Conference On Applied Mathematics, Oklahoma (1992), 317–330. 19. Saberi-Nadjafi, J. and Dahiya, R.S., Certain Theorems On N -dimensional Laplace Transformations and Their Applications, Proc. of Eighth Annual Conference On Applied Mathematics, Oklahoma (1992), 245–258. 74 R. S. Dahiya & Jafar Saberi-Nadjafi 20. Saberi-Nadjafi, J. and Dahiya, R.S., Theorems on N -dimensional Laplace transformations for the solution of Wave equations, (submitted for publication). 21. Saberi-Nadjafi, J., Laplace transform pairs of N -dimensionsl, Appl. Math. Lett., (to appear). 22. Sneddon, I.N., The Use of Integral Transforms, McGraw-Hill Book Company, New York, 1972. 23. Stromberg, K.R., Introduction to Classical Real Analysis, Wadsworth International Group, Belmount, California, 1981. 24. Voelker, D. Und Doetsch, G., Die Zweidimensionale Laplace Transformation, Verlag Birkuäuser Basel, 1950. R. S. Dahiya Department of Mathematics Iowa State University Ames, IA 50011, USA E-mail address: dahiya@iastate.edu Jaffar Saberi-Nadjafi Department of Mathematics, Ferdowsi, University of Mashhad Mashhad, Iran